GYY4137 ameliorates blood brain barrier damage by inhibiting autophagy mediated occludin degradation in cardiac arrest and resuscitation - Pengyu Duan; Xiaoyan Li; Yonghong Bi; Weiyu Feng; Zhehao Jin; Xiaoqian Zhang; Guanghui He; Da An; Zhibin Wen; Bing Zhang (Scientific Reports)
Abstract Cardiopulmonary resuscitation (CPR) after cardiac arrest (CA) is an important cause of neurological impairment and leads to considerable morbidity and mortality. The stability of the blood-brain barrier (BBB) is crucial for minimizing secondary neurological damage and improving long-term prognosis. However, the precise mechanisms and regulatory pathways that contribute to BBB dysfunction after CPR remain elusive. GYY4137 is an innovative hydrogen sulfide slow-release agent with excellent properties as a hydrogen sulfide substitute. The aim of this study was to investigate the protective effects of GYY4137 on CA/CPR and the underlying mechanisms of BBB protection. The effects of GYY4137 on systemic inflammation, BBB integrity, and autophagy were evaluated using a mouse CA/CPR model. The underlying mechanisms of occludin changes associated with GYY4137 were investigated using oxygen-glucose deprivation / reoxygenation (OGD/R) model. ELISA, neurological function and other tests showed that GYY4137 ameliorates systemic inflammation and neurological prognosis. Western blotting, transwell migration and tube formation assays showed that GYY4137 improves BBB function both in vivo and in vitro. The detection of autophagy flow and protein degradation pathways showed the inhibition of occludin reduction by GYY4137 was mainly achieved by suppressing autophagy mediated degradation. Taken together, GYY4137 may improve BBB dysfunction following CPR by increasing occludin content. This effect was achieved by inhibiting autophagic degradation rather than promoting synthesis. GYY4137 also mitigated systemic inflammation and improved neurological outcomes after CA/CPR. In summary, our study provides valuable insights into protecting the integrity of BBB and improving neurological outcomes after CPR.